The structural properties of full-length annexin A11 - Dudas, Erika F.; Tully, Mark D.; Foldes, Tamas; Kelly, Geoff; Tartaglia, Gian Gaetano; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2024)
Annexin A11 (ANXA11) is a calcium-dependent phospholipid-binding protein belonging to the annexin protein family and implicated in the neurodegenerative amyotrophic lateral sclerosis. Structurally, ANXA11 contains a conserved calcium-binding C-terminal domain common to all annexins and a putative intrinsically unfolded N-terminus specific for ANXA11.Little is known about the structure and functions of this region of the protein. By analogy with annexin A1, it was suggested that residues 38 to 59 within the ANXA11 N-terminus could form a helical region that would be involved in interactions. Interestingly, this region contains residues that, when mutated, may lead to clinical manifestations.In the present study, we have studied the structural features of the full-length protein with special attention to the N-terminal region using a combination of biophysical techniques which include nuclear magnetic resonance and small angle X-ray scattering. We show that the Nterminus is intrinsically disordered and that the overall features of the protein are not markedly affected by the presence of calcium. We also analyzed the 38-59 helix hypothesis using synthetic peptides spanning both the wild-type sequence and clinically relevant mutations. We show that the peptides have a remarkable character typical of a native helix and that mutations do not alter the behaviour suggesting that they are required for interactions rather than being structurally important. Our work paves the way to a more thorough understanding of the ANXA11 functions.